Penerapan Metode Tri-N dalam pembelajaran berdiferensiasi berbasis PjBL untuk meningkatkan hasil belajar IPA - Trinaini, Rizki Damajatu; Kusuma, Adhi; Santosa, Nevo (Literal: Disability Studies Journal, 2024)
The students' low science learning outcomes indicated that the learning quality was still inadequate. It underlies this study to increase the science learning outcomes through the implementation of differentiated learning and Tri-N (niteni, nirokke, nambahi) using the PjBL model with card media. This study uses the Classroom Action Research (CAR) method of the Kemmis and Taggart model, consisting of planning, implementation, observation, and reflection in two cycles. 32 students of class VIII A of SMP N 1 Bantul were the subjects of this study. The results showed a significant increase in student learning outcomes. At the pre-cycle stage, the overall completion percentage was only 41% with an average score of 70.31. After the first cycle implementation, the completion percentage increased to 63% with an average score of 75.83. Further improvement occurred in the second cycle, where the overall completion percentage reached 91% with an average score of 85.31. These results indicate that the applied learning method is effective in improving students' science learning outcomes and provides important implications for improving the quality of learning in class VIII A of SMP N 1 Bantul.